IMPLEMENTASI STRATEGI PEMBELAJARAN AKTIF DALAM MENINGKATKAN PRESTASI BELAJAR AKIDAH AKHLAK PESERTA DIDIK MADRASAH TSANAWIYAH MIFTAHUL HUDA KECAMATAN LEMPUING JAYA KABUPATEN OGAN KOMERING ILIR - Sodik; Achmad Asrori; Rina Setyaningsih (UNISAN JURNAL, 2025)
This study aims to determine the implementation of active learning strategies in improving learning achievement in the subject of Akidah Akhlak for students at Madrasah Tsanawiyah (MTs) Miftahul Huda, Lempuing Jaya District, Ogan Komering Ilir Regency. The background of this study is based on the need to create more interactive, meaningful, and student-centered learning, as well as addressing the low participation of students in the learning process in the subject of Akidah Akhlak. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of active learning strategies at MTs Miftahul Huda is carried out through various models such as group discussions, role plays, mind maps, and problem-based learning that are adapted to the character of the Akidah Akhlak material. Teachers act as facilitators, encouraging direct student involvement in the learning process. This strategy has been proven to increase motivation, critical thinking skills, and a deeper understanding of the concepts of faith and morals. This improvement has a positive impact on student achievement, as evidenced by evaluation scores, active participation during learning, and reinforcement of positive behaviors in daily life. Thus, active learning strategies are an effective approach to improving the quality of Aqidah Akhlak learning at the madrasah.